To investigate the effect of oxygen-driven salbutamol combined with methylprednisolone on bronchial asthma from the perspective of serum molecular markers - Lu; Zhang, Xiao; Ju, Yuanyuan; Yang, Xin (Journal of Medical Biochemistry, 2025)
Objective: This study explores the application of oxygen-driven salbutamol (SA) combined with methylprednisolone (MP) in bronchial asthma (BA) from the perspective of objective clinical markers, including serum inflammatory response, oxidative stress response, immunoglobulin, and pulmonary ventilation function. Methods: A retrospective analysis was performed on 207 pediatric BA patients admitted to our hospital between January 2022 and January 2025. Of them, 114 children received MP combined with SA nebulization (control group), and 93 children received MP combined with oxygen-driven SA (observation group). The pulmonary ventilation function, inflammatory mediators (HIF-1α, IL-4, IL-6, IL-8 and TNF-α), stress response indicators (SOD, NO, ET-1 and MDA) and immunoglobulin (IgE, IgA, IgM and IgG) were detected and compared before and after treatment. Results: Post-treatment, the observation group demonstrated superior pulmonary ventilation function and significantly lower levels of inflammatory mediators (HIF-1α, IL-4, IL-6, IL-8, and TNF-α) compared to the control group (P<0.05). Regarding stress response, the SOD level in the observation group was higher after treatment, while the levels of NO, ET-1, and MDA were lower (P<0.05). In addition, IgE was lower and IgA was higher in the observation group after treatment (P<0.05). Conclusion: The combination of oxygen-driven SA and MP is more effective in mitigating inflammatory, stress responses and optimizing immune function in pediatric BA patients.